The Correlation between Rheumatoid Factor, Chloroquine Phosphate in Osteoarthritis - S. Saleh, Eman (Iraqi Journal of Pharmaceutical Sciences, 2017)
Osteoarthritis (OA) is a series of aggressive destructive inflammatory processes. Synovitis is common both at an early and a late phase. This disease may be uniquely singular in some site but phylogenetically related at some point in time to produce a common outcome of dysfunction, disability, socioeconomic destruction and sometimes socioeconomic failure. Articular cartilage, subchondral bone and synovial membrane are the site of major abnormalities in this disease process. Rheumatoid factor (RF) represents one of the routine laboratory tests that made for all patients have joint complaints.Chloroquine phosphate (CQP) is agent belong to disease modifying osteoathritic drugs (DMOADs). Chloroquine and their derivatives have been used for their anti-inflammatory effect in juvenile chronic arthritis, Sjogren,s syndrome, discoid and systemic lupus erythematosus.The aim of this trial depend on using this drug in osteoarthritic patients for two months then estimate the level of RF check and RF(A,G,M).The result showed a significant correlation between CQP and RF check as well as RF type M in patients suffered from OA, so the level of these two parameters are decreased significantly in period of treatment thus leads to ameliorate the patients status and the joints pain will decreased. Key words: Chloroquine, osteoarthritis, rheumatoid factors.